Minat Meneliti Dosen Dan Mahasiswa Terhadap Kajian Ilmu Hubungan Internasional - Machya Astuti Dewi; Sri Issundari (Jurnal Paradigma, 2014)
For years no signi cant progress in conducting research of the lecturers and students of International Relations Department UPN “Veteran” Yogyakarta. This phenomenon encourage the researchers to seek the roots why it was happened. To know the answer, the researchers distributed questionnaires for student and did some in- depth interview with lecturers and students of department of International Relations UPN ‘Veteran” Yogyakarta.Additional data collected from academic reports, workshop reports, research reports of department of International Relations, journals and articles of relevant topics. The result shows that the low motivation doing research caused by internal and external factors. The internal factor is that the lecturers or students have low self-motivation because they realize conducting research is dif cult and not interesting one, and it spend too much time. External factors derives from the lack of socialization, lack of training and tutorial, and lack of rewards or incentive for doing research. Department of International Relations UPN “Veteran” Yogyakarta will improve and intensify the socialization of research incentive programs, regularly conduct training program of preparing research proposal, to help lecturers and student in preparing proposal, and facilitate sharing forum how to get incentive research.